Association between a laboratory-based frailty index and mortality of critically ill patients with acute pancreatitis: a retrospective study - Zou, Zhichao; Li, Zhe; Wan, Qihai; Wang, Qianqian; Yu, Yi (Frontiers in Nutrition, 2025)
BackgroundAcute pancreatitis (AP) is associated with significant global mortality and morbidity. Frailty, which can be assessed through clinical indicators and life history, is known to impact adverse outcomes across different medical conditions. The frailty index derived from laboratory tests (FI-Lab) is a novel approach to the quantification of frailty. This study sought to investigate the relationship between the FI-Lab and mortality among critically ill patients with AP.MethodsWe utilized data on patients diagnosed with AP from the Medical Information Mart for Intensive Care-IV database. The FI-Lab was calculated using a specific set of laboratory parameters indicative of physiological disturbances. The primary outcomes examined were 30-day and 90-day mortality rates. Multivariate Cox regression was used for the statistical analysis, with adjustments for age, gender, Acute Physiology and Chronic Health Evaluation II scores, and other variables. Propensity matching scores were used to ensure the robustness of our findings.ResultsA total of 1,116 AP patients were included in the analysis (mean age = 58.4 years; 57.9% male). Each 0.1 increment of FI-Lab was found to increase the risks of 30-day and 90-day mortality by 30% (hazard ratio (HR) = 1.30, p < 0.001 for both). The propensity score matching (PSM) analysis validated these results. The FI-Lab demonstrated an association with acute kidney injury and the requirement for continuous renal replacement therapy. However, these associations were not significant after the PSM analysis.ConclusionAn elevated FI-Lab was associated with higher mortality rates among critically ill AP patients. Randomized controlled trials are needed to confirm these findings and to explore their clinical implications.